Toward Remote Object Control Based on Python for Symbian S60 - I Made Murwantara; Fanny Sinthia; Fransiscus Ati Halim (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
Nowadays mobile phones can be used to do various things, such as recording or watching videos,listening to music, and scheduling. With recent developments in communication technology, mobile phones iscapable to communicate with another device. A global standard to accomplish is Bluetooth. Using Bluetooth, amobile phone can communicate with other devices. The exchange of data between compatible devices is handledby the Bluetooth protocol. This makes it easy for the programmer to develop various wireless applications onmobile phones which support Bluetooth. This paper presenting the use of Bluetooth to control the movement ofan object in a computer using a mobile phone based on Symbian S60, using Python.Keywords: Symbian, S60, Bluetooth, Python, Remote Object Control.